Upaya Perlindungan dan Pemeliharaan Telur Penyu di Yayasan Raksa Bintana, Pantai Batu Hiu, Pangandaran - Damayanti, Fis'ari; Junianto (Samakia : Jurnal Ilmu Perikanan, 2023)
Turtles are reptiles whose lives are almost entirely in the sea. They are able to migrate long distances for several purposes, one of which is laying eggs. One of the places turtles like to lay their eggs is Batu Hiu Beach. At Batu Hiu Beach there is also a turtle hatchery called the Raksa Bintana Foundation. Turtles themselves have been included in the red list on the IUCN and Appendix I CITES due to natural and human threats. The purpose of this research is to find out procedures for evacuating, protecting and caring for turtles at the Raksa Bintana Turtle Conservation Foundation, Batu Hiu Beach, Pangandaran. The method used is a qualitative descriptive method. This foundation carries out turtle conservation starting from the discovery of eggs until the turtles can be released back into the sea. Efforts to transfer (evacuate) the eggs are carried out in less than 12 hours and are incubated in semi-natural hatching nests for 40-60 days. Based on research by the Raksa Bintana Foundation, carrying out the transfer, incubation and maintenance processes was appropriate, resulting in 85% hatching success.